Creating Digital Literature through Transformational Leadership; Challenges and Solutions - Sudrajat, Dadang; Dikananda, Arif Rinaldi; Rahaningsih, Nining; Cakranegara, Pandu Adi; Putra, Purniadi (JURNAL AL-TANZIM, 2022)
This study aims to analyze and understand the principal's transformational leadership in realizing digital literacy. This study uses a qualitative approach to the type of phenomenology. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out through several stages: data reduction, data presentation, and conclusion drawing or verification. The results showed that; transformational leadership strategy in increasing digital literacy by holding mini workshops and digital literacy examples. The challenges and solutions in transformational leadership are that teachers are still technology literate and not wholeheartedly in studying digitalization and inadequate internet access. This research has implications for the importance of designing educational institutions oriented toward developing digital literacy in responding to the challenges and demands of the times.